Representasi Karya A.A. Navis Melalui Arsitektur Metafora Pada Perancangan Gedung Apresiasi Sastra Di Padang Panjang - Irsyad Rahim Putra; Mira Dharma Susilawati; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
House of literature appreciate come to support the environment which supporting the literature growth in West Sumatera. This building have function as creativity area. A place for gathering and as place for litterateurs to interact with one another, and also as a reading area for visitors and researchers. So that, it can rise their interest in appreciate of literature. Due to historical and strategic position, so, Kota Padang Panjang choose as site. Meanwhile, Robohnya Surau Kami by A.A. Navis, a writer born in Padang Panjang, become planning concept. The characteristic and value in that short-story displayed again as a house of literature appreciate through architecture metaphor. House of literature appreciate likened as Robohnya Surau Kami through transforming the literature elements on that short-story into architecture perspective. Transformation is done with metaphor method. Generally, it developed physical form building which came from that short-story title, mass shape come from conflict I short-story, landscape that described short-story background, and optimize the facilities to support individual activities, but still blending around as a form of application of the short-story theme.Keywordrs : House of literature appreciate , Robohnya Surau Kami, Architecture Metaphor